2020
DOI: 10.1007/s43154-020-00021-6
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Learning-Based Robotic Grasping

Abstract: Purpose of Review This review provides a comprehensive overview of machine learning approaches for vision-based robotic grasping and manipulation. Current trends and developments as well as various criteria for categorization of approaches are provided. Recent Findings Model-free approaches are attractive due to their generalization capabilities to novel objects, but are mostly limited to top-down grasps and do not allow a precise object placement which can limit their applicability. In contrast, model-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(108 citation statements)
references
References 76 publications
2
105
0
1
Order By: Relevance
“…With the exception of visual perception approaches, Luo et al ( 2017 ) and Wang C. et al ( 2020 ) exhibit there are many other perception methods can help improve robot performance. Caldera et al ( 2018 ), Kroemer et al ( 2019 ), Li and Qiao ( 2019 ), and Kleeberger et al ( 2020 ) focus on the overview of robot manipulation methods based on deep learning. Mohammed et al ( 2020 ) and Zhao W. et al ( 2020 ) introduce the techniques in robot learning on the basis of reinforcement learning.…”
Section: Proposed Taxonomymentioning
confidence: 99%
“…With the exception of visual perception approaches, Luo et al ( 2017 ) and Wang C. et al ( 2020 ) exhibit there are many other perception methods can help improve robot performance. Caldera et al ( 2018 ), Kroemer et al ( 2019 ), Li and Qiao ( 2019 ), and Kleeberger et al ( 2020 ) focus on the overview of robot manipulation methods based on deep learning. Mohammed et al ( 2020 ) and Zhao W. et al ( 2020 ) introduce the techniques in robot learning on the basis of reinforcement learning.…”
Section: Proposed Taxonomymentioning
confidence: 99%
“…Later researches introduced vision recognition of micro/ nano-components and learning algorithms applied to recognition and tracking of micro-objects [35] presents a complete review on learning-based approaches to perform general gripping operations at the macro-scale. To enhance dexterity and optimize the grasping trajectories, authors in [36] [37•] exploited physical models of grasping forces and pull-off forces during micro-manipulation operations using search algorithms for a real-time application which computes the gripping trajectory in less than 0.1 s. van Vuuren JJ et al [38] propose a learning-based methodology for identifying novel objects and evaluating different candidate grasping strategies for an optimal grasping and handling which might be applied to the manufacturing of consumer electronic products.…”
Section: Models and Algorithms Towards Adaptable Gripping Operationsmentioning
confidence: 99%
“…they extract the information from sample data in order to detect the grasp pose without having to be analytically programmed [7]. The following paragraphs are focused on a brief categorization of data-driven methods, since they have, in most cases, already been shown to outperform the analytic approaches to the grasping point detection in terms of computational complexity and accuracy [8], [9]. For analytic approaches, the surveys of various methods can be found in [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some approaches deal only with grasping of a single separated object, while others are able to handle grasping in a dense clutter [18]. A comprehensive review of various categorizations of data-driven approaches can be found in the recent work of Kleeberger et al [9].…”
Section: Introductionmentioning
confidence: 99%